2022
DOI: 10.1080/19317611.2022.2099499
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexuality in Aotearoa/New Zealand: Factors and Sexual Response Associated with Masturbation

Abstract: Objectives Sexual health includes the state of physical, emotional, mental, and social well-being related to sexuality. Masturbation is an important sexual activity with many potential benefits which has gained considerable interest in sexuality research in the past twenty years; however, this research is the first of its kind within the Aotearoa/New Zealand context. In this in-depth investigation, we examined frequencies of, reasons for, and activities during masturbation as well as the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…Although the current study operates on a different definition of sexual satisfaction, Regnerus et al ( 2017 ) found that subjective contentment with the recent frequency of sex was a good predictor of masturbation frequency. Furthermore, much research has suggested that overcoming anxious feelings and reducing stress are common motivations for masturbation (Csako et al, 2022 ; Kalmbach et al, 2014 ; Rowland et al, 2020 ). Thus, our findings suggest that while there were significant associations between masturbation with general sexual satisfaction, anxiety, and stress, conclusions regarding the directionality of these relationships should not be drawn at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study operates on a different definition of sexual satisfaction, Regnerus et al ( 2017 ) found that subjective contentment with the recent frequency of sex was a good predictor of masturbation frequency. Furthermore, much research has suggested that overcoming anxious feelings and reducing stress are common motivations for masturbation (Csako et al, 2022 ; Kalmbach et al, 2014 ; Rowland et al, 2020 ). Thus, our findings suggest that while there were significant associations between masturbation with general sexual satisfaction, anxiety, and stress, conclusions regarding the directionality of these relationships should not be drawn at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show a negative correlation between masturbation and relationship satisfaction (Santtila et al 2007; Wright et al 2021), quality (Dekker and Schmidt 2002; Corona et al 2010), happiness (Perry 2020a), intimacy (Carvalheira, Træen and Stulhofer 2015), emotional satisfaction with the partner (Randolph et al 2015), trust (Costa and Brody 2007), passion (Costa and Brody 2007), and other relationship parameters. The one exception encountered is a study that showed a small-to-moderate positive but significant correlation between the frequency of masturbation and satisfaction with primary relationship in women (Csako et al 2022). But otherwise, there seems to be a consensus in the literature that masturbation negatively correlates with many aspects of relationship health.…”
Section: Introductionmentioning
confidence: 99%